Exploring the Socio-Economic Dynamics of Batik Giriwangi Artisans: A Study on Local Wisdom and Challenges - Indra Iryanto Nur Hidayat; Wahyu Purnomo; Guntur Andi Pamungkas (PT. Hidayat Muda Intelektual, 2025)
This study examines the socioeconomic dynamics of Batik Giriwangi artisans in Kebondalem Kidul, Prambanan, focusing on how they adapt to industrial challenges while preserving traditional knowledge. This study investigates how craftspeople adjust to cultural, technical, and economic shifts using qualitative methods and a case study methodology. Participatory observations, in-depth interviews, and document analysis were used to gather data. According to the results, artisans persevere via creativity in goods and community cooperation despite obstacles in the areas of workforce regeneration, digital advertising, and growing raw material costs. This study emphasizes how crucial internet marketing tactics, vocational training, and government assistance are to bolstering the Batik Giriwangi sector.